CONTEMPORARY CHALLENGES IN APPLYING OF THE MODIFIED MODEL CAPM WITH COUNTRY RISK PREMIUM IN EMERGING ECONOMIES - Petrović, Dragana (International Journal of Economic Practice and Policy, 2017)
Modern approach in determining the expected return of foreign investors` investments is based on the evaluation investment in capital asset-CAPM (Capital Asset Pricing Model). In order to use the CAPM model for calculating the expected return of foreign investors in growing economies, it is developed the extended model CAPM with the risk premium in the country. This variant of the CAPM model has been used for estimating the cost of capital. This is the expected return on a portfolio of the company`s stocks in less developed countries. Those countries have certain problems and factors of risk investment. This research examines the limitations and shortcomings in the application of the extended model with country risk premium, during the calculation of the cost of capital in the less developed economies. We present possible models to overcome those problems and also a need for upgrading of modified CAPM model with a risk premium of the country which, beside risk of the country (CR) must have a discount for the “advantage of the country“.
Keywords: growing markets; CAPM model; country risk; equity risk premium